2012
DOI: 10.4172/2155-9600.s5-001
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Resveratrol in Inhibiting Cancer and Slowing Aging

Abstract: Resveratrol (3, 4', 5 trihydroxystilbene) is a natural phytoalexin produced in response to injury by various plants including grapevines, berries and peanuts. Extensive evidence has indicated the beneficial effects of resveratrol on neurological, hepatic, cardiovascular, and inflammatory diseases. One of the most striking biological activities of resveratrol is its cancer chemopreventive potential. It has been shown recently that resveratrol blocks multiple processes during carcinogenesis including tumor initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 139 publications
(153 reference statements)
1
21
0
Order By: Relevance
“…LC MS/MS analysis showed that Hardaliye mostly contained gallic acid and resveratrol. The rate of these polyphenols were consistent with studies conducted with grape juice or wine [28]. Gallic acid and resveratrol are polyphenols found in grape, tea, wine and berries.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…LC MS/MS analysis showed that Hardaliye mostly contained gallic acid and resveratrol. The rate of these polyphenols were consistent with studies conducted with grape juice or wine [28]. Gallic acid and resveratrol are polyphenols found in grape, tea, wine and berries.…”
Section: Discussionsupporting
confidence: 71%
“…Their anti-aging, anticancer and anti-inflammatory effects have been demonstrated in vast variety of studies [29,30]. Digalloylresveratrol, a synthetic ester of gallic acid and resveratrol has been demonstrated that dose-dependently induces apoptosis and inhibites the transition from S to G2/M phase of the HT-29 colon cancer cells [28]. Gallic acid has also induced apoptosis of colon adenocarcinoma cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds possess a variety of biological activities and have been used as anticancer, antioxidant, anti inflammatory agents [12][13][14]. Numerous publications reported the therapeutic potential of resveratrol in various ailments, including cancer, heart, diabetes, stroke and Alzheimer disease [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that bioactive dietary components are strong epigenetic modulators that appear to play a part in prevention of breast cancer [ 8 10 ]. A growing group of studies has indicated that nutritional factors play an important role in many human diseases and have been identified and evaluated for their activities against cancer [ 11 , 12 ]. One such food source is berries, which are rich sources of a wide variety of antioxidant phytochemicals such as stilbenes.…”
Section: Introductionmentioning
confidence: 99%
“…Stilbenes are natural phenolic compounds, consisting of resveratrol and pterostilbene. Resveratrol (3, 4′, 5 trihydroxystilbene) is a natural phytoalexin, synthesized by plants such as grapevines, berries and peanuts in response to an injury [ 12 ].…”
Section: Introductionmentioning
confidence: 99%